2007
DOI: 10.11606/issn.1678-4456.bjvras.2007.26653
|View full text |Cite
|
Sign up to set email alerts
|

Estudo histológico e imunoistoquímico do sistema nervoso central de cães naturalmente infectados por Leishmania (Leishmania) chagasi

Abstract: The present study aimed to characterize the histopathological alterations and to detect, by immunohistochemistry, the presence of amastigote forms of Leishmania in CNS tissue of dogs with and without neurological clinical signs of the disease. Two groups of animals were used: the first was composed of 18 dogs with visceral leishmaniasis without clinical evidence of neurological involvement, and the second, composed of 21 dogs with visceral leishmaniasis and neurological symptoms. The most frequent histopatholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 14 publications
(25 reference statements)
3
5
0
Order By: Relevance
“…Similar to the findings of studies performed on the brains of dogs with CanL, inflammation was not related to the presence of amastigotes in the tissue ( 30 , 41 43 ). One hypothesis would be that chronic systemic inflammation resulting from L. infantum infection, with production of cytokines and chemokines, could alter barrier permeability ( 44 46 ).…”
Section: Discussionsupporting
confidence: 85%
“…Similar to the findings of studies performed on the brains of dogs with CanL, inflammation was not related to the presence of amastigotes in the tissue ( 30 , 41 43 ). One hypothesis would be that chronic systemic inflammation resulting from L. infantum infection, with production of cytokines and chemokines, could alter barrier permeability ( 44 46 ).…”
Section: Discussionsupporting
confidence: 85%
“…Inflammatory reaction during canine visceral leishmaniasis was also observed by Ikeda et al [11], who analyzed brains of dogs with and without neurological signs and described degenerative alterations with neuronophagia, gliosis, leptominingitis, vascular congestion and the presence of a perivascular lymphoplasmacytic infiltrate and areas of micro-hemorrhages.…”
Section: Discussionmentioning
confidence: 53%
“…Other studies, despite the observation of histopathological alterations in the CNS of dogs during visceral leishmaniasis, failed to verify the presence of Leishmania amastigotes [11, 19, 20, 2325]. Some authors explain these contradictory findings by the chronicity of the disease, arguing that the presence of Leishmania in the CNS has generally been demonstrated in dogs with an earlier infection, either because of delayed diagnosis or by the choice of treatment for the infected dogs, as in two studies in the Mediterranean region [11, 24]. In fact, here we observed that animals that presented amastigote forms in the CNS had clinical signs such as cachexia and the presence of skin lesions, observed in the chronic phase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations